Covalency in Actinide Compounds. Issue 19 (31st January 2021) - Pace, Kristen A.; Klepov, Vladislav V.; Berseneva, Anna A.; zur Loye, Hans‐Conrad
Abstract: Covalency in actinides has emerged as a resounding research topic on account of the technological importance in separating minor actinides from lanthanides for spent nuclear fuel processing, and utilization of their distinct bonding properties has been realized as a route towards overcoming this challenge. Because of the limited radial extent of the 4f orbitals, there is almost no 4f electron participation in bonding in lanthanides; this is not the case for the actinides, which have extended 5f orbitals that are capable of overlapping with ligand orbitals, although not to the degree of overlap as in the d orbitals of transition metals. In this concept paper, a general description of covalency in actinide compounds is provided. After introducing two main approaches to enhance covalency, either by exploiting increased orbital overlap or decreasing energy differences between the orbitals causing orbital energy degeneracy, the current state of the field is illustrated by using several examples from the recent literature. This paper is concluded by proposing the use of actinide chalcogenides as a convenient auxiliary tool to study covalency in actinide compounds. Abstract : Organometallics tricks for actinide extended structures : Covalency in actinide complexes has long been studied for both its fundamental interest and potential applications for minor actinides separation. In this concept paper, covalency in actinides is introduced and illustrated with several examples from the current literature. It is shown that actinide chalcogenide extended structures may serve as auxiliary platforms for studying covalency.